Intravascular lymphoma: an unusual cause of rapid cognitive decline and the role of brain biopsy. (21st August 2014) - Chaturvedi, Sujata; Pant, Ishita; Kushwaha, Suman; Jha, Deepak Kumar
Abstract : Intravascular lymphoma (IVL) is a rare extra nodal variant of non Hodgkin's lymphoma characterised by neoplastic lymphoid cells growing inside the lumina of medium and small vessels. IVL limited to the central nervous system (CNS) is an extremely rare condition as IVL is usually found with systemic lesions. Most cases of IVL are not diagnosed until post mortem because of variable clinical presentation and non-specific laboratory findings. Even if diagnosed early the disease is clinically aggressive and usually fatal, even with early detection and treatment. We present a case of a 37-year-old woman with a short history of behavioural abnormality, rapidly progressive cognitive decline and seizures. There were no cutaneous manifestations. Diagnosis was established only after the brain biopsy. The case is presented for the rarity of its presentation and role of brain biopsy in diagnosis.